Implementasi Continuous Quality Improvement (CQI) dalam Pengembangan Budaya Mutu Pembelajaran Berbasis Teknologi di Madrasah Ibtidaiyah - Riana Auliya; Satrio Pandales; Ahmad Zainuri; Frika Fatimah Zahra (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research is intended to examine the application of Continuous Quality Improvement (CQI) in fostering a culture of quality within technology-based learning at Madrasah Ibtidaiyah.. CQI is a continuous approach that emphasizes systematic quality improvement by means of iterative stages of planning, execution, assessment, and continuous follow-up. Within the frameworl of Islamic, elementary pedagogy, the application of CQI is essential to enhance learning quality that is adaptive to digital technological developments. This study employs a qualitative approach through conductinga literature review and performing a conceptual analysis of technology-based learning practices. The results reveal that the implementation of Continuous Quality Improvement (CQI) can foster a quality culture by integrating technology into the learning process, improving teachers’ competencies, utilizing interactive digital media, and conducting continuous data-based evaluations. Furthermore, leadership support, infrastructure availability, and the active participation of all school stakeholders are key factors for successful CQI implementation. Therefore, CQI plays a strategic role in creating innovative, effective, and sustainable quality-oriented learning in Madrasah Ibtidaiyah